Pendampingan Desa Wisata Politeknik Pariwisata Bali di Desa Wisata Cemagi - Diwyarthi, Ni Desak Made Santi; Witarsana, I Gusti Agung Gede; Pratiwi, Kadek Andita Dwi; Suastini, Ni Made; Jata, I Wayan; Adyatma, Prastha; Adinda, Clearesta; Pratama, I Wayan Adi (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of community service activities is to carry out the socialization of the tourist village program, which was carried out by the Hospitality Management Study Program, Bali Tourism Polytechnic, on June 23, 2023. The implementation of community service activities is carried out through the delivery of material related to the socialization of government regulations on tourist villages, the scope and steps in managing tourist villages, including accommodation related to tourist villages, in an effort to identify the various strengths, weaknesses, obstacles and opportunities faced by Cemagi Tourism village. The Cemagi Tourism Village study involved 25 community members, accommodation business managers, village government, and village community organizations. The results found that Cemagi Tourism Village has the strengths of beautiful and unique natural resources and a calm atmosphere, weaknesses in the form of tourism facilities and products that characterize it, opportunities in the form of infrastructure development and promotion that support tourism growth and increase attractiveness for visitors, and threats in the form of competition with other tourist destinations in Bali that are close to each other, and environmental impacts due to the surge in visitors can damage the natural preservation of Cemagi village